Implementasi Business Perfomance Dashboard Untuk Memonitoring Booking Pembiayaan Pada Pt. Internusa Tribuana Citra Multi Finance Jakarta - Susanto, Januar; Thantawi, Ahmad Muhammad (IKRA-ITH Informatika : Jurnal Komputer dan Informatika, 2024)
PT Internusa Tribuana Citra Multi Finance, data management for performance monitoring is currently still not computerized or still manual. So that performance monitoring is still less efficient and accurate. The use of the Business Intelligence Roadmap method and dashboards in the Power BI application can help monitor performance in data processing, data analysis and facilitate decision making and KPI (Key Performance Indicators) measurements can be measured quickly and precisely with visual graphics. After implementing the Business Intelligence Roadmap using the Power BI application, it becomes more effective and efficient, and providing data reports to stakeholders in a visual graph runs as expected and can facilitate stakeholders in monitoring performance using the dashboard that has been created.